Traditional Chinese medicine and its components effectively reduce resistance mediated by immune checkpoint inhibitors - Guo, Mingxin; Fang, Wentong; Hu, Zhiqiang (Frontiers in Immunology, 2024)
Immunotherapy has become a global focus in cancer treatment and research, with promising results from targeting immune checkpoints in tumors like non-small cell lung cancer, colon cancer, and melanoma. However, resistance to immune checkpoint inhibitors (ICIs) remains a significant challenge. Traditional Chinese medicine (TCM), known for its low toxicity and minimal side effects, shows promise in enhancing cancer treatment when combined with modern therapies. This study reviews recent research on ICIs resistance mechanisms and highlights TCM’s potential in overcoming this resistance, aiming to improve ICIs efficacy while minimizing toxicity.